THE EFFECT OF ENTREPRENEURSHIP EDUCATION AS A MODERATION ON STUDENTS' INTEREST IN ENTREPRENEURSHIP BASED ON THEORY OF PLANNED BEHAVIOR - Abdul Haris; Agung Nugroho Jati; Arif Julianto Sri Nugroho; Darupratomo Darupratomo; Endang Eko Djati S.; Dandang Setyawanti; M. Gunawan Setyadi (International Journal of Economics, Business and Accounting Research (IJEBAR), 2023)
This research aimed to test whether the learning model obtained by entrepreneurship education students can strengthen attitude variables, subjective norms and perceived behavioral control of Unwidha undergraduate students' entrepreneurship interest. The research design was carried out using quantitative methods that explained the causal relationship between one variable and the other variables to be tested. The hypothesis test was formulated in a model using the Structural Equation Model multivariate test. The population in this research are all Unwidha undergraduate students who have a strong interest in entrepreneurship. The sampling technique was carried out by purposive sampling of 100 student respondents. The results of the analysis found that entrepreneurship education as a moderator influences student entrepreneurship motivation and the overall model in the SEM fit test. The research results can serve as a basis for making quality entrepreneurial learning models by adding aspects of real entrepreneurial practice for Unwidha undergraduate students